Identical twins with differing forms of ventricular pre-excitation. Issue 2 (February 1978) - Bennett, D H; Gribbin, B; Birkhead, J S
Abstract : Identical 10-year-old twins, both with electrocardiograms showing a short PR interval and a normal QRS complex but with dramatically different electrophysiological characteristics, are described. One twin experienced episodes of rapid palpitation and on one occasion was resuscitated from ventricular fibrillation. An intracardiac electrophysiological study confirmed the presence of an atrioventricular nodal bypass tract and in addition revealed the presence of an accessory atrioventricular pathway, thus demonstrating that the patient had both the Lown-Ganong-Levine and Wolff-Parkinson-White syndromes. Re-entry tachycardia and atrial fibrillation, with a very rapid ventricular rate, were precipitated. After treatment with amiodarone, the patient became asymptomatic and a repeat study showed that the features of the atrioventricular nodal bypass tract were no longer present and though re-entry tachycardias using the accessory atrioventricular pathway could still be induced, their rates were slower than before treatment. The other twin, in spite of an identical surface electrocardiogram, was asmymptomatic. An electrophysiological study showed the features of an atrioventricular nodal bypass tract but there was no evidence of additional atrioventricular accessory connections and a tachycardia could not be induced.